2020
DOI: 10.2478/jvetres-2020-0060
|View full text |Cite
|
Sign up to set email alerts
|

Colistin resistance of non-pathogenic strains of Escherichia coli occurring as natural intestinal flora in broiler chickens treated and not treated with colistin sulphate

Abstract: IntroductionA significant threat to public health is presented by antibiotic-resistant strains of bacteria, selective pressure on which results from antibiotic use. Colistin is an antibiotic commonly used in veterinary medicine, but also one of last resort in human medicine. Since the 2015 discovery in China of the mcr-1 gene encoding colistin resistance in Enterobacteriaceae, other countries have noted its presence. This study was to find the mcr-1 gene prevalence in E. coli isolated from poultry slaughtered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
1
6
1
Order By: Relevance
“…Recently, Sun et al [ 34 ] demonstrated a significant presence of tigecycline-resistant E. coli strains from raw meat bearing the tet (X) gene. It should also be highlighted that in our investigation, all E. coli strains were susceptible to colistin differently than what was observed in other studies [ 35 , 36 , 37 ]. However, it should be specified that colistin, after being administrated for a long time as a prophylactic and therapeutic agent, is currently in off-label use in Italy and it was banned as a growth promoter [ 35 ].…”
Section: Discussioncontrasting
confidence: 80%
“…Recently, Sun et al [ 34 ] demonstrated a significant presence of tigecycline-resistant E. coli strains from raw meat bearing the tet (X) gene. It should also be highlighted that in our investigation, all E. coli strains were susceptible to colistin differently than what was observed in other studies [ 35 , 36 , 37 ]. However, it should be specified that colistin, after being administrated for a long time as a prophylactic and therapeutic agent, is currently in off-label use in Italy and it was banned as a growth promoter [ 35 ].…”
Section: Discussioncontrasting
confidence: 80%
“…In our present study, regarding the obtained MIC values for the selected antimicrobial agents, all the investigated mcr-1- positive E. coli strains showed MDR profile (resistance to at least three antimicrobial classes). Similar results were obtained by other authors from Brazil, China, Argentina, and Poland [ 29 31 , 35 , 60 ]. Monte et al [ 29 ] showed that most of the mcr-1- positive E. coli isolates exhibited an MDR phenotype and carried genes conferring resistance to aminoglycosides, quinolones, sulfonamides, and tetracyclines.…”
Section: Discussionsupporting
confidence: 91%
“…A significantly higher percentage of colistin-resistant E. coli strains in Poland was confirmed by studies conducted in 2017–2018, where the presence of the mcr-1 gene occurring in the normal microbiota of chicken broilers, both treated and untreated with colistin sulfate, was tested. Isolates containing the mcr-1 gene were obtained in 11.27% of strains from untreated flocks and in 19.54% of isolates obtained from flocks treated with colistin [ 35 ]. In Europe, the prevalence of E. coli strains isolated from poultry and carrying the mcr-1 gene ranged from 1.5% in the Netherlands [ 28 ] to 13.95% in Portugal [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An association between animal polymyxin consumption and colistin resistance in E. coli from poultry and swine has been suggested in an EU report (ECDC et al ., 2017), but the long‐term impact of ongoing colistin reduction measures on food‐producing farms and, consequently, on food safety (e.g., poultry meat) is still poorly defined. On the other hand, the persistence of colistin resistance and mcr genes, including in non‐treated poultry flocks (Poland) (Majewski et al ., 2020) or pigs (Great Britain) (Duggett et al ., 2018), suggests that other factors beyond colistin consumption might contribute to their selection, but this needs to be further explored and understood.…”
Section: Resultsmentioning
confidence: 99%